2004
DOI: 10.1016/j.molcel.2004.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Androgen Receptor Interdomain and Coactivator Interactions Suggests a Transition in Nuclear Receptor Activation Function Dominance

Abstract: The androgen receptor (AR) is required for male sex development and contributes to prostate cancer cell survival. In contrast to other nuclear receptors that bind the LXXLL motifs of coactivators, the AR ligand binding domain is preferentially engaged in an interdomain interaction with the AR FXXLF motif. Reported here are crystal structures of the ligand-activated AR ligand binding domain with and without bound FXXLF and LXXLL peptides. Key residues that establish motif binding specificity are identified thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
290
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(307 citation statements)
references
References 49 publications
15
290
2
Order By: Relevance
“…Evaluation of the crystallographic structure of a peptide containing the LXXLL sequence bound to AR shows that the LXXLL motif adopts an a-helical structure and that the side chains of the three leucines at the i, i þ 3 and i þ 4 positions interact with the hydrophobic pocket in the AF2 domain of AR 24,25 . We used the rigid and pre-organized structure of a bis-benzamide scaffold 26 to design the peptidomimetic D2 that mimics the LXXLL motif and disrupts the interaction between AR and NR box containing proteins such as PELP1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of the crystallographic structure of a peptide containing the LXXLL sequence bound to AR shows that the LXXLL motif adopts an a-helical structure and that the side chains of the three leucines at the i, i þ 3 and i þ 4 positions interact with the hydrophobic pocket in the AF2 domain of AR 24,25 . We used the rigid and pre-organized structure of a bis-benzamide scaffold 26 to design the peptidomimetic D2 that mimics the LXXLL motif and disrupts the interaction between AR and NR box containing proteins such as PELP1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NATURE COMMUNICATIONS | DOI: 10.1038/ncomms2912 ARTICLE Discussion AR requires interactions with its coregulator proteins to actively engage in transcriptional activity 31,32 . Given that many coregulators interact with the AR through motifs containing the consensus LXXLL motif 24 , where L is Leucine and X is any amino acid, we rationally designed peptidomimetics that imitate the LXXLL motif with the aim of disrupting necessary AR-mediated PPIs and thereby inhibit AR signalling and the survival of prostate cancer cells. Previous attempts to generate LXXLL-based peptide drugs have been unsuccessful, predominantly due to issues with cell permeability and degradation.…”
Section: D2 Inhibits Ar Expression In Human Tumours Cultured Ex Vivomentioning
confidence: 99%
“…Like other nuclear receptors (NRs), AR is a transcription factor regulating target-gene expression in a liganddependent manner (2,16). Cognate ligand binding induces conformational changes predominantly in helix 12 of AR LBD, which enhances transcriptional activity by forming a liganddependent AF-2 binding interface for coactivators (17). Wilson and colleagues demonstrated that the interdomain interaction between AF-1 in NTD and AF-2 in LBD (N/C interaction) leads to AR stabilization and slower ligand dissociation (18,19).…”
mentioning
confidence: 99%
“…In the absence of ligand, AR is located primarily in the cytoplasm as an inactive complex with heat shock proteins. Upon androgen binding, AR undergoes conformational change, translocates into the nucleus, and recruits coactivator complexes for transactivation through direct DNA binding to androgen response elements (AREs) in AR target gene promoters (9,10). As observed in wild-type AR, polyQ-AR mutants reportedly translocate into the nucleus and recruit coactivator complexes to the AREs in a liganddependent manner (11).…”
Section: Spinal and Bulbar Muscular Atrophy (Sbma) Is A Neurodegeneramentioning
confidence: 99%